Diagnóstico económico de los microcréditos de crecimiento otorgados al sector comercial en el Banco Nacional de Fomento Sucursal Calceta, periodo 2013-2014. - Franco Salvatierra, Virginia E. (2016)
The objective of the study was to establish a diagnosis of growth of microcredit granted to the commercial sector by the National Bank of development for the analysis of the economic development of the beneficiaries in the Bolívar canton in the period 2013-2014. For its compliance is planned three phases, the first was identify those customers to who is les granted them credits, determining a shows of 69 merchants; the second consisted in the design of the questionnaire by the technical survey, which focused on assessing the fate of micro-credit, verifying most of the granted power flow was applied to increase business, buying merchandise and tools which gave effect to the commercial activities; This generated stability and increase of the volume of the trading profits. the third stage set up an analysis of the socio-economic impact of the beneficiaries of microcredit granted by the Bank, where applying the inductive-deductive method it was found that investment increased activities and effect the linkage of labour, in this case study recruitment corresponded to family members and people with a social link, as well as improve their lifestyles whose economic sources are business. Thus determined that the credits granted by the National Bank of development allowed the development and revival of business, as well as boost the economy for the direct and indirect beneficiaries of the loan portfolio.